2015
DOI: 10.1017/s0003055415000441
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Persistent Terrorism on Political Tolerance: Israel, 1980 to 2011

Abstract: How do persistent terrorist attacks influence political tolerance, a willingness to extend basic liberties to one's enemies? Studies in the U.S. and elsewhere have produced a number of valuable insights into how citizens respond to singular, massive attacks like 9/11. But they are less useful for evaluating how chronic and persistent terrorist attacks erode support for democratic values over the long haul. Our study focuses on political tolerance levels in Israel across a turbulent 30-year period, from 1980 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
68
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(77 citation statements)
references
References 54 publications
7
68
2
Order By: Relevance
“…All of these variables were measured using the common measurements in Israel. In addition, past work has suggested that right‐wingers have a stronger tendency toward homophily (Garrett et al, ) and that political tolerance declines during armed conflict (Peffley, Hutchison, & Shamir, forthcoming). Therefore, we also included the following variables in our analyses:…”
Section: Methodsmentioning
confidence: 99%
“…All of these variables were measured using the common measurements in Israel. In addition, past work has suggested that right‐wingers have a stronger tendency toward homophily (Garrett et al, ) and that political tolerance declines during armed conflict (Peffley, Hutchison, & Shamir, forthcoming). Therefore, we also included the following variables in our analyses:…”
Section: Methodsmentioning
confidence: 99%
“…As such, "the occurrence of new environmental cues" has the potential to induce shifts in individuals' (and groups') values and attitudes over time (Bardi and Goodwin, 2011, 278; see also Peffley et al, 2015). Importantly, these individual-level changes can easily reverberate into the relation between association memberships and individuals' attitudes even when the 'same' individuals remain embedded in the 'same' association.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…It is not easy to imagine a more fear-inspiring terror than year-afteryear suicide bombings and rocket attacks. Peffley, Hutchison, and Shamir's (2015) study of political tolerance is thus unique, tracking levels of political tolerance in the Israeli public, over a three decade period, from 1980 to 2012, in the face of repeated and sustained terror attacks (Peffley, Hutchison, & Shamir, 2015; Figure 2).…”
Section: /11mentioning
confidence: 99%